Fluid-Structure Interaction Analysis On Aircraft Wing Intergrated With Wing Tip Device - Tan, Yao Bin (Universiti Sains Malaysia, 2021)
Wing tip device is a common device nowadays on an aircraft to improve the aerodynamic performance of the aircraft. Wing tip device’s purpose is usually to reduce the induced drag by diminishing the downwash of the flow around the wing tip. The optimal design to improve the aerodynamic performance of wing tip and the fluid-structure interaction (FSI) effect on the aircraft wing is still a wide field to be discovered and should be studied in an ample scope. This report is carried out to study the aerodynamic performance of the designed blended split wing tip along with comprehending the study of FSI analysis to investigate the structural deformation and stresses on the wing integrated with wing tip device. The research is conducted in a subsonic and transonic region with speed varies from 0.2 Ma to 0.6 Ma. Thereafter, the aerodynamic analysis is performed at 0° angle of attack (AOA) to 16° angle of attack at 0.2 Mach. Numerical method of 3D Computational Fluid Dynamics (CFD) analysis is used to analyze the aerodynamic performance of the proposed split wing tip design and comparison is done to justify the improvement. Besides, 2D aerodynamic analysis is used to validate and comprehend the 3D CFD analysis. A total of 3 wings with no wing tip, split wing tip and blended split wing tip is analyzed using ANSYS CFD. To inspect the structural stresses on the wing, a one-way FSI approach is included in this report. The structural stress at the wing root, mid-span area and wing tip is studied and compared between the three wing models at different Mach number and angle of attack. The finding indicates that the proposed blended split wing tip design have a drawback in aerodynamic performance at Mach number of 0.2, 0.4 and 0.6. However, this wing tip design benefits the aerodynamic performance when AOA is varying from 0 to 16 while Mach number is maintained at 0.2. It has an overall increase of 6.684% in the aerodynamic performance when compared with wing with no wing tip. From the structural point of view, the blended split wing tip device can relieve the high concentrated stress in the stress raiser to a preferred region in the top winglet.